Craniospinal intradural arachnoid cyst. Issue 804 (October 1992) - Bhatia, S.; Thakur, R. C.; Devi, B. I.; Radotra, B. D.; Kak, V. K.
Abstract : A patient with an uncommonly situated congenital intradural arachnoid cyst is reported. The cyst extended from the cervical spinal canal into the posterior cranial fossa and was posterolateral to the spinal cord. The patient's initial complaint was urinary hesitancy. The location of the cyst is unique and the presenting complaint rare.